An Expanding Foam‐Fabric Orthopedic Cast. Issue 9 (13th March 2022) - Root, Samuel E.; Sanchez, Vanessa; Tracz, Jovanna A.; Preston, Daniel J.; Zvi, Yoav S.; Wang, Kemble; Walsh, Conor J.; Homer‐Vanniasinkam, Shervanthi; Whitesides, George M.
Abstract: Traditional orthopedic casting strategies used in the treatment of fractured limbs, such as fiberglass and plaster‐based tapes, suffer from several drawbacks, including technically challenging molding for application, occurrence of skin complications, and the requirement of a potentially hazardous oscillatory saw for removal, which is frightening for pediatric patients. This work presents the design and evaluation of a foam‐fabric cast (FFC) to overcome these drawbacks by integrating strategies from soft materials engineering and functional apparel design. A fabric sleeve is designed to enable the reactive injection molding of a polymer foam and provide a form‐fitting orthopedic cast for the human forearm—with sufficient mechanical reinforcement to stabilize a fractured limb. Through testing with a replica limb and human subjects with a range of forearm volumes, the FFC application process is demonstrated and characterized. The thermal, pressural, chemical, and hygienic safety are comparable to or safer than existing clinical technologies. The FFC weighs only ≈150 g, is water resistant, and represents a robust alternative to traditional casts that can be i) manufactured at a large scale for a low cost; ii) applied to patients simply, rapidly (≈5 min), and reliably; and iii) removed easily with a pair of scissors. Abstract : An orthopedic cast is designed using the expansion and solidification of a polymer foam within a fabric sleeve. The design allows for a custom‐fitting cast to be applied safely and rapidly, without the need for manual molding; worn comfortably and hygienically, while providing sufficient mechanical support for stabilization of the limb; and removed safely, and easily, without an oscillatory cast‐saw.